Problematika Penerapan Undang-undang Jaminan Produk Halal di Indonesia - Moh. Kusnadi (ISLAMIKA, 2019)
This paper aims to resolve challenges and controversies faced by the Halal Law and provide a transition process before the Halal Law regime and after the enactment of the Halal Law. This paper also looks at the readiness and effectiveness as well as the method of determination made under the Halal Law when the time comes that this Halal Law will be fully implemented on October 17, 2019. The analytical method used uses qualitative analysis using literature review as data collection. The theory used is the effectiveness of the legal system by Lawrence M. Friedman who oversees the effectiveness of three criteria, namely structure, substance, and legal culture. The results of this paper show that the Halal Law has many problems before it is fully implemented in October 2019. First, the structure of this law is not ready to undergo a halal process system. Second, the substance of the Halal Law is burdensome and rather burdensome and incomplete because there are many supporting regulations that have not yet been ratified. In addition, the results also show how Halal Act determines the halalness of a product. Still using the same method before the enactment of the Halal Law that relies on the MUI Fatwa Assembly.